Promoting Competencies Of The Brazilian Common National Curriculum With Chess - Brusamolin, Valerio; Rejane Stival Pedroni (Զանգակ հրատ.)
This article explores the potential of chess as a pedagogical tool to enhance competencies outlined in the Brazilian National Curriculum (BNCC). With an increasing focus on comprehensive education, schools are seeking innovative strategies to promote student development. Drawing on the BNCC's ten general competencies, this study investigates the relationship between chess practice in schools and the cultivation of these competencies. We demonstrate how chess can contribute to students' cognitive, social, and emotional growth through a comprehensive literature and educational theory analysis. From fostering critical thinking and problem-solving skills to promoting empathy and cooperation, chess offers a holistic approach to education. By aligning with the principles of the BNCC, incorporating chess into school curricula can enrich the learning experience and prepare students for active citizenship in a complex world. This study underscores the importance of integrating playful and engaging activities like chess into educational practices to support students' holistic development.
Keywords: Education